Effect of Nutrition Education Intervention on Knowledge Attitude and practice of mothers/caregivers on infant and young child feeding in Shabelle (Gode) Zone, Somali Region, Eastern Ethiopia - Abdi Guled, Rashid; Mamat, Nik Mazlan; Balachew, Tefera; Mohd. Abu Bakar, Wan Azdie; Assefa, Nega (IIUM Press, International Islamic University Malaysia, 2018)
Optimal Infant and Young Child Feeding is very important for their health, growth and development. The impact of long term nutrition education intervention on child feeding in underprivileged community is not well documented. Therefore, this study was designed to document the effect of nutrition education intervention on knowledge, attitude and practice of mothers/caregivers towards optimal infants and young child feeding in Shabelle Zone of Somali Region. With regards to the materials and the methods, a randomized controlled trial study was conducted in August, 2015. Data were collected from 404 participants, after eight months of nutrition education intervention. SPSS version 20 software were used. A Chi-square and Fishers exact tests for categorical variables, and t-test for continues variables were used. Out of the total 415 participants assessed at baseline study, 404 were secured in the post intervention study. The majority (>80%) of the participants in both groups were illiterate, and housewives. The intervention group had shown statistical significant improvement in knowledge, attitude and practice of the mothers/caregivers (p<0.05) compared to control group in all tests; independent sample t-test mean score difference of the difference (p<0.001), and paired sample t-test mean score in intervention group (p<0.001). At the end, the nutrition education intervention was found effective in improving mothers/caregivers behaviours related to child feeding practices. Therefore, nutrition education intervention should be further scaled up and adapted to other areas in the Region.